Transitional labour markets and flexicurity from the Finnish labour market point of view - Heikki Räisänen; Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
This article presents a conceptual approach related to the European flexicurity discussion, the Transitional Labour Market theory and its main assumptions. Our aim is to bring this analytic framework into the discussion and to clarify some central aspects by introducing empirical findings concerning the case of Finland. The transitional labour market theory is a useful approach to analyse the combinations of flexibility and security, as it is not only a national model concerning one country, but a comprehensive conceptual system emphasising labour market transitions during the lifecourse. The particularities of the Finnish labour market dynamics suggest that one must be aware of a 'dual transitional labour market' and, accordingly, that one should differentiate between labour market policies. – – Dieser Beitrag liefert einen konzeptionellen Ansatz für die europäische Flexicurity Debatte - die Theorie der Übergangsarbeitsmärkte und ihre wesentlichen Annahmen. Unser Ziel ist, diesen analytischen Bezugsrahmen zur Diskussion zu stellen und einige zentrale Aspekte zu klären, indem empirische Befunde für den Fall von Finnland dargestellt werden. Die Theorie der Übergangsarbeitsmärkte erweist sich als ein hilfreicher Ansatz, um Kombinationen von Flexibilität und Sicherheit zu analysieren, da sie nicht als Repräsentation eines einzelnen nationalen Modells angelegt ist, sondern als umfassendes System von Arbeitsmarktübergängen im Lebensverlauf. Die Besonderheiten der finnischen Arbeitsmarktdynamik legen nahe, von einem 'dualen Übergangsarbeitsmarkt' zu sprechen und die arbeitsmarktpolitischen Maßnahmen entsprechend zu differenzieren.
Keywords: 330